IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN ONLINE MATERI PERSAMAAN DAN FUNGSI KUADRAT DI KELAS IX-A MTS.AL-BIDAYAH - Eki Dwi Pebriyanti; M. Afrilianto; Tina Rosyana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research is a classroom action research. The purpose of this study was to determine the implementation of the scientific approach in online learning of quadratic equations and functions in class IX-A MTs.Al-Bidayah. The subjects of this study were 35 students of class IX-A MTs.Al-Bidayah for the academic year 2020/2021. The instruments used are essay test questions, teacher and student observation sheets, interviews and questionnaires. The steps of this research consist of: (1) Planning, (2) Implementation of action, (3) Observation, (4) Evaluation. At the stage of the first cycle, the teacher was less than optimal in applying the learning approach, did not motivate students, and did not organize the learning time well. Furthermore, in the second cycle stage, the weaknesses that occur in the first cycle can be corrected by the teacher. In addition, more and more students are able to take part in learning by using a scientific approach, solving problems, and asking the teacher for things they do not understand. The results of this study indicate that the scientific approach in online learning can be applied and has a positive influence on student learning outcomes in class IX-A MTs.Al-Bidayah.